TINJAUAN YURIDIS PELAKSANAAN KEWENANGAN PEMERINTAH KOTA PEKANBARU DALAM PENATAAN BANGUNAN TEMPAT TINGGAL DI SEMPADAN SUNGAI SIAK - Binsar Bersahabat Hutasoit; Emilda Firdaus; Dodi Haryono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The writing of this law is about a house located on the river border in SiakRegency. The formulation of the problem is whether the existence of a house on theSiak river border in Pekanbaru City is in accordance with Pekanbaru CityRegional Regulation No. 7 of 2020 concerning the Pekanbaru City DevelopmentPlan for 2020-2040 and what steps are being taken by the government to overcomethis problem. This legal research aims to identify, study, and analyze houseslocated in the riparian area of the river in Siak Regency. This Legal article is anempirical research. Based on the results of the study it can be concluded that thehouse which is located on the border of the Siak river in Pekanbaru City violatesPekanbaru City Regional Regulation No. 7 of 2020 concerning the Pekanbaru CityDevelopment Plan for 2020-2040 and until now there has been no governmenteffort to overcome this problem.Keywords: River border, Siak river, house located in the river border area.